(untitled) (El Hilo de la Fabula, 2022)
During the Argentine 80’s, there was an abundance of travel accounts (Cané, Estrada, Groussac, etc.), a genre that could be defined as the work of men -who left impressions on the occasion of their travels, generally to Europe, for pleasure or diplomatic work- if Eduarda Mansilla’s Recuerdos de viaje (1882) had not been published. This work by one of the most important writers of 19th century Rioplatense culture is the only account of an experience in the United States during the Civil War written by a woman of the period. The text is relevant because it provides nuances, from its inherent and permeating gender perspective, allowing the statutes of the aesthetic journey, topicalised by critics to address the men of the 80’s, to be de-centred. In her journey, a sophisticated woman narrator, with her savoir faire, admiring the civil and labour freedoms of American women, yet not always, dwells on the leitmotif of cultural otherness when analysing the politics and ethnic conflict. The fine irony of the multi-focal gaze of the foreigner, porteña and woman of the world, who is, at the same time, the woman narrator; overflows the text with contrasts where the Union is the axis of distancing and model seduction.